Classification of avulsion fractures of the fifth metatarsal base using three‐dimensional CT mapping and anatomical assessment: a retrospective case series study - Wenbao He; Haichao Zhou; Yingqi Zhang; Tao Yu; Jiang Xia; Youguang Zhao; Yunfeng Yang; Bing Li (Journal of Foot and Ankle Research, 2022)
Abstract Background To clarify the injury mechanism of the avulsion fracture of the fifth metatarsal combining 3‐dimensional (3D) fracture mapping with anatomical measurements. Methods Two hundred twenty‐two patients with the avulsion fractures of the fifth metatarsal base, who were admitted to our hospital from August 2015 to August 2020. The computed tomography (CT) scans were used to generate the 3‐D images of all mapped fracture lines for the avulsion fractures of the fifth metatarsal base were compiled in an overall 3D image. The fifth metatarsal base of 8 unpaired lower limbs of adult Asian frozen cadaveric specimens were also dissected to observe and measure the specific locations of the attachment points of the peroneus brevis, lateral band of the plantar fascia, and peroneus tertius to the fifth metatarsal base. Results Based on the type of fracture line produced and the specific locations of the attachment points of the tendons or fascia, the avulsion fractures of the fifth metatarsal base can be classified into three types: type I predominantly involves the action of the lateral band of the plantar fascia; type II predominantly involves the action of the peroneus brevis; type IIIA involves the joint action of the peroneus brevis and lateral band of the plantar fascia with one fracture line, and type IIIB involves the joint action of the peroneus brevis and lateral band of the plantar fascia with two fracture lines. Conclusion The lateral band of the plantar fascia and peroneus brevis play a major role, either separately or together, in avulsion fractures of the fifth metatarsal base. With this knowledge, we propose a novel classification based on the injury mechanism, which can serve as a reference for clinical treatment and diagnosis. Level of evidence Level III, retrospective case series.